Salt and potassium intake among adult Ghanaians: WHO-SAGE Ghana Wave 3 - Elias K. Menyanu (BMC Nutrition, 2020)
Abstract Though Ghana has high hypertension prevalence, the country lacks current national salt consumption data required to build and enhance advocacy for salt reduction. We explored the characteristics of a randomly selected sub sample that had valid urine collection, along with matched survey, anthropometric and BP data (n = 839, mean age = 60y), from the World Health Organization’s Study on global AGEing and adult health (WHO-SAGE), Ghana Wave 3, n = 3053). We also investigated the relationship between salt intake and blood pressure (BP) among the cohort. BP was measured in triplicate and 24 h urine was collected for the determination of urinary sodium (Na), potassium (K), creatinine (Cr) and iodine levels. Hypertension prevalence was 44.3%. Median salt intake was 8.3 g/day, higher in women compared to men (8.6, interquartile range (IQR) 7.5 g/day vs 7.5, IQR 7.4 g/day, p <  0.01), younger participants (18–49 y) compared to older ones (50+ y) (9.7, IQR 7.9 g/day vs 8.1, IQR 7.1 g/day, p <  0.01) and those with higher Body Mass Index (BMI) (> 30 kg/m2) compared to a healthy BMI (18.5–24.9 kg/m2) (10.04, IQR 5.1 g/day vs 6.2, IQR 5.6 g/day, p <  0.01). More than three quarters (77%, n = 647) of participants had salt intakes above the WHO maximum recommendation of 5 g/d, and nearly two thirds (65%, n = 548) had daily K intakes below the recommended level of 90 mmol. Dietary sodium to potassium (Na: K) ratios above 2 mmol/mmol were positively associated with increasing BP with age. Population-based interventions to reduce salt intake and increase K consumption are needed.